Entrepreneurial orientation and funding decisions on the financial performance of small and medium industries - Hapsari, Putu Indah; Wiksuana, I Gusti Bagus; Artini, Luh Gede Sri; Dewi, Sayu Ketut Sutrisna (Indonesian Journal of Multidisciplinary Science, 2024)
Small and Medium Industries play an important role in relation to economic growth in Asian countries. The empowerment of SMEs is very strategic because of its great potential in driving economic activities, as well as being a source of income in improving community welfare (Sum, et al, 2004). To explore the factors affecting the sustainability of SMEs, the study conducted a systematic literature review of relevant articles published between 2015 and 2023, focusing on entrepreneurial orientation and financial performance. The findings of this study reveal that the ability of a company's entrepreneurial orientation has a significant influence on financial performance. Companies with a high level of entrepreneurial orientation tend to innovate products consistently, dare to consider business risks, and act proactively against possible environmental changes. Companies with a high level of entrepreneurial orientation are always trying to find new opportunities and strengthen their competitive position in carrying out business activities in the market. Moreover, it emphasizes that the development of the concept of entrepreneurial orientation is indispensable in SMEs. This is important because the personal attributes of the owners that make up the entrepreneurial orientation have a strong influence on financial performance. The dimensions of entrepreneurial orientation can be reflected in attitudes and behaviors, such as autonomy, risk, innovation, and aggressive competition by placing personal attributes on business owners. Here, entrepreneurial orientation is directly related and has a strong impact in encouraging companies to perform better.